Welcoming and protecting: brief considerations on forms of international protection in the European Union - an interdisciplinary perspective - PACHECO, Fátima; BALTAZAR, Isabel (Revista Jurídica Portucalense, 2023)
Situations of generalized violation of human rights and individual and severe persecution made us aware of the need to guarantee victims of such situations the international protection they need. The essence of such protection consists in granting a right of reception; the right not to be returned to the State of origin; and, furthermore, the need to provide procedural and judicial guarantees for its implementation. Such an aspiration can be realized by granting such individuals the International Status of Refugees. The present work reflects on the content of this right, highlighting its shortcomings and presenting the answers that the Union has created to fulfill this desideratum.